Hadith #2544 - Sunan Abi Dawud - Abu Ahmed al-Mu'dab الحسين بن محمد بن بهرام - أبو علي المؤدب; ibn Abbas; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Prophet (ﷺ) said: Keep to every sorrel horse with a white blaze and white on the legs, or dark bay with a white blaze. He then mentioned something similar. Muhammad ibn al-Muhajir said: I asked him: Why was a sorrel horse preferred? He replied: Because the Prophet (ﷺ) had sent a contingent, and the man who first brought the news of victory was the rider of a sorrel horse.
Grade: Da'if

Hadith #4858 - Sunan Abi Dawud - Abu Ahmed al-Mu'dab الحسين بن محمد بن بهرام - أبو علي المؤدب; al-Walid bin Abi Hisham الوليد بن أبي هشام زياد; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; ibn Mas'ud; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin Yahya bin Faris al-Dhahli محمد بن يحيى بن فارس الذهلي; Muhammad bin Yusuf al-Faryabi محمد بن يوسف الفريابي; Zayd bin Za'id'h زيد بن زائدة ويقال; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan Abi Dawud)
A similar tradition has also been transmitted by Abu Hurairah from the Prophet (ﷺ) through a different chain of narrators.
Grade: Sahih